Dynamic general equilibrium modelling for forecasting and policy : a practical guide and documentation of MONASH - Dixon, Peter B.; Rimmer, Maureen T. (Amsterdam ; Boston : Elsevier, 2002)
The book is aimed at giving practical guidance to potential model builders describing the use of MONASH a dynamic computable general equilibrium model of the Australian economy.
Includes bibliographical references (p. 309-323) and indexes.
nmn 30/04/13
Loans
Keywords: Economic policy; Statics and dynamics (Social sciences); Economic forecasting; Economics; Equilibrium (Economics)